False alarm? Estimating the marginal value of health signals - Iizuka, Toshiaki; Nishiyama, Katsuhiko; Chen, Brian; Eggleston, Karen (Journal of public economics, 2021)
•We study efficiency of response to health signals from mandatory checkups.•Regression discontinuity analysis of diabetes thresholds reveals heterogeneous effects.•Among the general population, utilization increases but no evidence of improved health.•For high risks, medical care increases and health outcomes improve, cost-effectively.•Health signals can improve welfare if thresholds are appropriate and follow-up care well targeted. We investigate the marginal value of information in the context of health signals that people receive after checkups. Although underlying health status is similar for individuals just below and above a clinical threshold, treatments differ according to the checkup signals they receive. For the general population, whereas health warnings about diabetes increase healthcare utilization, health outcomes do not improve. However, among high-risk individuals, outcomes do improve, and improved health is worth its cost. These results indicate that the marginal value of health information depends on setting appropriate thresholds for health warnings and targeting individuals most likely to benefit from follow-up medical care.